Development of a Web-Based Radar Monitoring and Failure Analysis System Integrated with the TopSky ATS - Syahrul, Syahrul; Tanaka, Hiroshi; Anderson, Michael (Yayasan Cendekiawan Digital Indonesia, 2026)
Radar is a crucial component of the Air Traffic Services system, supporting Air Traffic Controllers in monitoring aircraft movements and maintaining flight safety. At Airnav Indonesia Makassar Air Traffic Service Centre (MATSC) Branch, the radar disturbance recording process is still done manually, potentially leading to recording errors, reporting delays, and inefficiencies in technical evaluation. This study aims to develop a web-based radar disturbance monitoring and analysis system integrated with TopSky ATS that automatically detects, records, and visualises radar disturbances. The system is designed to recognise changes in radar status, calculate failure duration, record the number of disturbance events, and present this information in tables and dashboards in real time. Radar log data is obtained from the Control Work Position (CWP37) device via the TopSky Event Log, then parsed using the ASTERIX protocol categories 34 and 48, and stored in a MySQL database. The system was developed using the Waterfall model, while system evaluation was conducted through black-box testing and User Acceptance Testing. The results show that the system can accurately detect and display radar disturbance information in real time. The UAT, involving 10 technicians, demonstrated a user acceptance rate of 93.2%, categorised as very good. These findings demonstrate that the developed system can improve efficiency, accuracy, and timeliness in radar monitoring and support data-driven technical evaluations in air traffic services operations.